DESCRIPTION OF PATIENTS' COMPLIANCE IN ASEER REGION, KINGDOM OF SAUDI ARABIA - Alakhali, Khaled (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Medication non-adherence can cause impairments that interfere with self-care activities in individuals who suffer from multiple comorbid diseases that require careful management. The objective of this study is to assess and describe medication adherence in patients of Aseer Region of Kingdom of Saudi Arabia (KSA). Samples of 416 patients in the outpatient department at Abha General Hospital and Aseer Central Hospital are selected randomly. The patients were interviewed using seven a self-administered close-ended anonymous questionnaire. Only descriptive statistics is reported in this study for analyze the compliance category. The participants in the study were 71% (295 out of 416 patients) of participants were females, while 29% (121 out of 416) were males. The participants’ age ranges between 18-60 years. The adherence level was 85%. The major reasons for non-adherence were forgetfulness and feeling good. The study revealed the appropriate level of adherence by participants. The study also revealed that pharmacists and other healthcare professional intervention will help to improve further the medication adherence with possible fruitful therapeutic outcomes of the patients.Key words: Non-adherence patient, Kingdom of Saudi ArabiaMedication non-adherence can cause impairments that interfere with self-care activities in individuals who suffer from multiple comorbid diseases that require careful management. The objective of this study is to assess and describe medication adherence in patients of Aseer Region of Kingdom of Saudi Arabia (KSA). Samples of 416 patients in the outpatient department at Abha General Hospital and Aseer Central Hospital are selected randomly. The patients were interviewed using seven a self-administered close-ended anonymous questionnaire. Only descriptive statistics is reported in this study for analyze the compliance category. The participants in the study were 71% (295 out of 416 patients) of participants were females, while 29% (121 out of 416) were males. The participants’ age ranges between 18-60 years. The adherence level was 85%. The major reasons for non-adherence were forgetfulness and feeling good. The study revealed the appropriate level of adherence by participants. The study also revealed that pharmacists and other healthcare professional intervention will help to improve further the medication adherence with possible fruitful therapeutic outcomes of the patients.Key words: Non-adherence patient, Kingdom of Saudi Arabia